2016
DOI: 10.1039/c5ay03178h
|View full text |Cite
|
Sign up to set email alerts
|

Novel chromogenic selective sensors for aqueous cyanide ions under high water content and real sample analysis

Abstract: Novel chromogenic receptors (R1–R2) containing anthraquinone as the signalling unit and imidazole as the binding unit were designed to enhance the sensing action in an aqueous medium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 26 publications
(19 reference statements)
1
8
0
Order By: Relevance
“…The UV–vis titration studies of DTPH were performed with 10 –5 M sensor solution prepared in ACN and 10 –4 M CN – solution prepared in 9:1 ACN–H 2 O medium. Here, the occurrence of water probably inhibited the deprotonation upon addition of CN – . , From the absorption spectra, it was shown that the free sensor exhibited two peaks at 255 and 300 nm corresponding to the π–π* and n−π* transition, respectively, and the π–π* transition also corroborated with the time-dependent density functional theory calculation (Figure S13; Supporting Information). Upon steady addition of CN – to the sensor, a new peak was noticed to be emerged at 480 nm with simultaneous diminution of the initial peak and upsurge of the peak at 300 nm, affirming an charge-transfer transition within the −NH moiety of the sensor and CN – (Figure a).…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…The UV–vis titration studies of DTPH were performed with 10 –5 M sensor solution prepared in ACN and 10 –4 M CN – solution prepared in 9:1 ACN–H 2 O medium. Here, the occurrence of water probably inhibited the deprotonation upon addition of CN – . , From the absorption spectra, it was shown that the free sensor exhibited two peaks at 255 and 300 nm corresponding to the π–π* and n−π* transition, respectively, and the π–π* transition also corroborated with the time-dependent density functional theory calculation (Figure S13; Supporting Information). Upon steady addition of CN – to the sensor, a new peak was noticed to be emerged at 480 nm with simultaneous diminution of the initial peak and upsurge of the peak at 300 nm, affirming an charge-transfer transition within the −NH moiety of the sensor and CN – (Figure a).…”
Section: Resultssupporting
confidence: 62%
“…The foremost mechanism which can elicit an obvious color change of a sensor molecule by the interaction with an anionic species is the charge–transfer transitions, which triggers the alteration of the spectroscopic characters of the sensor and consequently changes its UV–vis spectrum . Moreover, the lesser hydration energy (Δ H hyd = −67 kJ mol –1 ) of CN – than that of F – (Δ H hyd = −505 kJ mol –1 ), AcO – (Δ H hyd = −375 kJ mol –1 ), and H 2 PO 4 – (Δ H hyd = −260 kJ mol –1 ) further helps to selectively recognize CN – in the pool of others competitive anions. ,, …”
Section: Introductionmentioning
confidence: 99%
“…The overall electron density around BDC is significantly enhanced that further causes a reduction in the energy gap between the molecular orbital of BDC; thus, the appearance of a new band occurs at a higher wavelength accompanied by a color change from pale yellow to dark brown. 57 Herein, −NO 2 as an electron-pulling chromophore was purposefully incorporated to increase the acidity of the amide protons and also the hydrogen-donor properties of the chemoreceptor. 58 The response of the chemoreceptor BDC toward the other environmentally encountered anions has been investigated (Figure S13 in the Supporting Information).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Owing to this, a partial positive charge is developed on the −NH unit of BDC and a negative one on the N atom of the CN – molecule that furthermore facilitates the charge transfer process owing to the push–pull effect. The overall electron density around BDC is significantly enhanced that further causes a reduction in the energy gap between the molecular orbital of BDC ; thus, the appearance of a new band occurs at a higher wavelength accompanied by a color change from pale yellow to dark brown . Herein, −NO 2 as an electron-pulling chromophore was purposefully incorporated to increase the acidity of the amide protons and also the hydrogen-donor properties of the chemoreceptor .…”
Section: Resultsmentioning
confidence: 99%
“…The adverse health consequences of ions such as cyanide, are well documented such as complications of vascular, visual, central nervous, cardiac, endocrine and metabolic systems. [1][2][3][4][5][6][7][8] Chemically, cyanide ion is a resilient nucleophile, sufficiently basic in nature, and can act as an ambidentate ligand and most importantly a pseudohalide. Cyanide is chosen as an exemplar since it nds widespread application in metallurgy, mining, electroplating and polymer synthesis.…”
Section: Introductionmentioning
confidence: 99%